Study on the potato market at the level of Romania in the period 2012-2017 - Eduard Alexandru Dumitru; Roxana Franzutti (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
Potato is a basic food for the Romanian consumer, and not because of the special nutritional qualities, but rather the consistency it has. Given the low level of living, in Romania it is an extremely consumed food, both in the urban environment, but especially in the rural area. Exceptional storage qualities cannot be left aside, offering the possibility of consumption even in the cold season. In 2017 (28 million euros), there was an increase of 80.3% compared to the value of imports registered in 2012 (16 million euros).
Keywords: Q13; Q17; 330; potatoes; vegetable sector; vegetables